2006
DOI: 10.1080/10284150600955164
|View full text |Cite
|
Sign up to set email alerts
|

A nonpungent component of steamed ginger - [10]-shogaol - increases adrenaline secretion via the activation of TRPV1

Abstract: We investigated the components of ginger that are involved in increasing body temperature. Gingerols ([6,8,10]-gingerols) and shogaols ([6,8,10]-shogaols) having different alkyl carbon chain lengths were targeted. All the gingerols and shogaols increased intracellular calcium concentration in rat transient receptor potential vanilloid subtype 1 (TRPV1)-expressing HEK293 cells via TRPV1. In this regard, the shogaols were more potent than the gingerols. Aversive responses were induced by [6]-, [10]-gingerol, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
50
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 29 publications
2
50
0
Order By: Relevance
“…Ginger may play a role in energy balance regulation by activating the transient-receptor potential vanilloid uncoupling pathway [3,11,12], implicated in the thermogenic effect of capsaicin [13]. However, consumption of a meal with ginger sauce did not increase post-prandial EE over a 2-h period to a greater extent than a similar meal without ginger [14].…”
Section: Introductionmentioning
confidence: 99%
“…Ginger may play a role in energy balance regulation by activating the transient-receptor potential vanilloid uncoupling pathway [3,11,12], implicated in the thermogenic effect of capsaicin [13]. However, consumption of a meal with ginger sauce did not increase post-prandial EE over a 2-h period to a greater extent than a similar meal without ginger [14].…”
Section: Introductionmentioning
confidence: 99%
“…At pro-apoptotic concentrations, 10-shogaol, an extract from ginger, was able to induce G(2)/M arrest and abnormal mitotic cell death that is associated with tubulin aggregation [19]. 10-Shogaol, the only non-pungent compound among the gingerols and shogaols, has the ability to stimulate the increase of adrenaline secretion [20]. Literature studies showed that the multiplication of free radicals in cells resulted in the suppression of cell viability, which implies that antioxidant exhibits relatively positive effects on cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…We identified capsiate from non-pungent red pepper and [10]-shogaol from ginger as TRPV1 agonists having low pungency which increased the adrenaline secretion and energy expenditure. [11][12][13] MGs as activators of TRPV1 may therefore be useful food ingredients to increase energy expenditure.…”
mentioning
confidence: 99%